Virtual screening of the inhibitors targeting at the viral protein 40 of Ebola virus. Issue 1 (December 2016) - Karthick, V.; Nagasundaram, N.; Doss, C.; Chakraborty, Chiranjib; Siva, R.; Lu, Aiping; Zhang, Ge; Zhu, Hailong
Abstract Background The Ebola virus is highly pathogenic and destructive to humans and other primates. The Ebola virus encodes viral protein 40 (VP40), which is highly expressed and regulates the assembly and release of viral particles in the host cell. Because VP40 plays a prominent role in the life cycle of the Ebola virus, it is considered as a key target for antiviral treatment. However, there is currently no FDA-approved drug for treating Ebola virus infection, resulting in an urgent need to develop effective antiviral inhibitors that display good safety profiles in a short duration. Methods This study aimed to screen the effective lead candidate against Ebola infection. First, the lead molecules were filtered based on the docking score. Second, Lipinski rule of five and the other drug likeliness properties are predicted to assess the safety profile of the lead candidates. Finally, molecular dynamics simulations was performed to validate the lead compound. Results Our results revealed that emodin-8-beta-D-glucoside from the Traditional Chinese Medicine Database (TCMD) represents an active lead candidate that targets the Ebola virus by inhibiting the activity of VP40, and displays good pharmacokinetic properties. Conclusion This report will considerably assist in the development of the competitive and robust antiviral agents against Ebola infection.